Integrating Asta Cita Values and Religious Moderation in Enhancing Students’ Digital Literacy in the Post-Truth Era - I Gede Suwindia; Ni Nyoman Kurnia Wati; Made Ferry Kurniawan (UNHI PRESS, 2025)
This study aims to analyze the effectiveness of integrating Asta Cita values and religious moderation in improving students’ digital literacy in the post-truth era. The phenomenon of the rapid flow of digital information often leads to the spread of disinformation and the degradation of ethical values among young people, necessitating a learning approach that is not only cognitive but also grounded in spiritual and moral values. This research uses a mixed method approach, involving two groups of students: a group that received Asta Cita value-based learning and religious moderation, and a group that did not participate in Asta Cita value-based learning and moderation. Quantitative data was obtained thru digital literacy tests, while qualitative data was collected thru observation and reflective interviews. The research results show that the experimental group experienced a significant improvement in digital literacy skills, particularly in the aspects of critical thinking, media ethics, and moderation awareness in technology use. The integration of Asta Cita values such as tat twam asi (empathy), dharma santosa (peace), and jana kerthi (social service) can foster a sense of responsibility and social sensitivity in digital interactions. Meanwhile, the application of religious moderation values strengthens students’ ability to objectively filter information and avoid extreme attitudes in responding to digital issues. Thus, this study concludes that integrating Asta Cita values and religious moderation into learning can be an effective strategy for building intelligent, ethical digital character rooted in national values in the post-truth era.